SERAT MADU TATA KRAMI DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER - Sunaryadi Sunaryadi (LITERA, 2013)
This study aims to reveal values in Serat Madu Tata Kramireflected in the philosophy of Joged Mataramand its relevance to character education. The data source was Serat Madu Tata Krami, K.P.H. Brongtodiningrat’s private collection. The work is in the form of macapat songs, written in Javanese using the Javanese alphabet in the Mataram style (the modernJavanese). This study employed the qualitative descriptive method. The findings show that the values in Serat Madu Tata Kramican serve as basic values for character education. The values are related to expectation, advice, suggestion, and belief that struggling for truth and virtue will always succeed. The teaching in Serat Madu Tata Krami cannot be separated from the philosophy of Joged Mataram, which holds the gallant values to faceall life problems using the philosophy of sawiji, greget, sengguh,and ora mingkuh.